Perbandingan Kinerja Keuangan Bank Konvensional dan Bank Syariah yang Listing di IDX Indonesia: Analisis dengan Metode Rgec - Novriyani Novriyani; Aris Triyono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to compare the financial performance of conventional banks and Islamic banks listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital). The study employed primary and secondary data obtained from financial reports and statistical data published by conventional and Islamic banks. The research method used was quantitative descriptive analysis and comparative analysis with a financial ratio approach based on the RGEC method. The results showed that the financial performance of conventional banks, namely PT Bank Negara Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, and PT Bank Rakyat Indonesia (Persero) Tbk, was categorized as healthy to very healthy based on the CAR ratio of 32.19%, NPF of 2.23%, ROA of 3.33%, FDR of 86.87%, and BOPO of 63.21%. Meanwhile, Islamic banks consisting of PT Bank Syariah Indonesia Tbk, PT Bank BTPN Syariah Tbk, and PT Bank Panin Dubai Syariah Tbk also demonstrated healthy to very healthy performance with a CAR ratio of 31.80%, NPF of 1.05%, ROA of 3.87%, FDR of 89.65%, and BOPO of 75.36%. This study is expected to contribute to stakeholders’ understanding of banking financial performance in Indonesia.